Determinan pengangguran usia muda: Studi kasus di pulau Jawa dan Sulawesi - Putra, Galang Ardian; Siti Aisyah (Nur Science Institute, 2021)
Youth unemployment is a challenge for development in Indonesia. As a country that is experiencing a demographic dividend, the issues of absorbing young workers are getting more attention. This study aims to analyze the effect of Gross Regional Domestic Product, provincial minimum wage, investment, inflation, and population on youth unemployment in provinces in Java and Sulawesi in 2011–2019. The analysis method used is panel data regression with the approach of the Random Effect Model (REM). The results show that the provincial minimum wage, inflation, and population have a positive and significant effect on youth unemployment in Java and Sulawesi in 2011–2019. Meanwhile, Gross Regional Domestic Product and investment proved to have no significant effect on youth unemployment.